Burn Model System educational outputs: Domestic and global dissemination - Gretchen J. Carrougher; Caitlin M. Orton; Barclay T. Stewart (Elsevier, 2024)
Knowledge translation and consumer testing aims to move research findings from scientists, professional journals, and conferences to the hands of end-users and organizations who use the information regularly. The purpose of this report is to outline the process by which the Burn Model System (BMS) has worked with the Model System Knowledge Translation Center (MSKTC) to develop and disseminate patient education materials to consumers. The National Institute on Disability, Independent Living, and Rehabilitation Research-funded BMS in collaboration with the MSKTC uses a multi-step process for developing and consumer-testing evidence-based/consensus-derived educational information prioritized by consumers. The final written products are made available in both English and Spanish at/below an 8th grade reading level. Products are disseminated through websites, clinical encounters, social media, and national/international engagement with clinicians and burn-related organizations. Written products are reviewed every five years to ensure they remain current and relevant. Number of online views for each product is a key measure of dissemination. Since 2011, the collaboration between the BMS and the MSKTC has produced or updated 22 educational factsheets, three videos, three infocomics, and one infographic. Collectively, these products have been viewed over two million times by people in 216 countries. Online views of all products have generally increased year-to-year. This process makes relevant health information accessible and understandable for consumers. As a result, Burn Model System informational products have been increasingly viewed by US and international consumers.